Loot [compact disc, unabridged] : how to steal a fortune - Watson, Jude (Scholastic Audiobooks, 2015)
On a foggy night in Amsterdam, a man falls from a rooftop to the wet pavement below. It's Archibald McQuinn, the notorious cat burglar, and he's dying. As sirens wail in the distance, Archie manages to get out two last words to his young son, March: "Find jewels." But March learns that his father is not talking about hidden loot. He's talking about Jules, the twin sister March never knew he had. No sooner than the two find each other, they're picked up by the police and sent to the orphanage.